Pemanenan air hujan untuk sistem irigasi dan kendali iklim mikro di greenhouse (State of the Art) - sudirman sirait; Yunisa Tri Suci; Edo Saputra; Saat Egra; Dwi Santoso (Balai Pelatihan Pertanian Jambi, 2023)
Several agricultural activities around the world emphasize the need to develop technology for cultivating plants in greenhouses that consumes low costs energy. Rainwater harvesting in areas with high rainfall is an alternative source of irrigation water for greenhouse plants. Rainwater harvesting results can be used in greenhouses as a source of fertigation water and microclimate control. Plants require an adequate amount of water on a continuous basis, and this is one of the factors that contribute to the success of greenhouse plant cultivation. The purpose of this article is to increase understanding of rainwater harvesting for irrigation systems and microclimate control in greenhouses. The results of rainwater harvesting from the rooftop greenhouse can meet 61.49-69% of the greenhouse's irrigation water needs. Microclimate reference, substrate moisture content, soil/planting media moisture content, and phyto-sensing can all be used to guide greenhouse irrigation. Rainwater harvested meets irrigation water quality criteria and can save money on irrigation costs. Furthermore, rainwater harvesting results can be used as a source of raw water for fertigation systems and microclimate control in greenhouses. Rainwater harvesting for greenhouse microclimate control can reduce temperatures by 1.3-3.6 °C and is less expensive than fan cooling systems.